Closed loop subspace system identification - Van Overschee, P.; De Moor, B. (Proceedings of the 36th IEEE Conference on Decision and Control, 1997)
We present a general framework for closed loop subspace system identification. This framework consists of two new projection theorems which allow the extraction of non-steady state Kalman filter states and of system related matrices directly from input output data. Three algorithms for the identification of the state space matrices can be derived from these theorems. The similarities between the theorems and algorithms, and the corresponding open loop theorems and algorithms in the literature are remarked on.